Effect of Atrazine, 2,4-D Amine, Glyphosate and Paraquat Herbicides on Soil Microbial Population (Journal of Environmental Microbiology and Toxicology, 2022)
Herbicides’ toxic impact on the non-target soil microorganisms which play roles in degrading organic matter, nitrogen and nutrient recycling and decomposition needs to be considered. In the present study, the effect of four (4) most commonly used herbicides, viz; atrazine, 2, 4- D amine, glyphosate and paraquat on soil microorganisms was assessed over a period of fifteen continuous days (exposure period). The herbicide treatments were the normal recommended field rate, (6.67 mg active ingredient per gram of soil for atrazine, 6.17 mg for 2, 4-D amine, 5.56 mg for glyphosate, and 2.46 mg for paraquat), half and double of the recommended field rates. Tables 4.1 through 4.5 showed the various heterotrophic bacterial colony counts obtained from the various treatments, ranging from the control (Day 1; no herbicide applied) to days 3, 6, 9 and 15 after the application of the various herbicides, respectively. Two general trends are readily observed: the first is that, upon application of the herbicide, the microbial growth steadily diminishes, up to the 6th day. However, from there it continues to increase till the end of the experiments (day 15). This applies to each herbicide. Firstly, the effect of the addition of the various herbicides was evaluated using two samples, a two-tailed Z-Test for means, at a 95% confidence interval, and the results showed that there is a difference in the bacterial counts before the application of the herbicides (Day 0) and immediately after (day 3), and the difference is statistically significant (Z = 3.32, Z critical = 1.96, P = 0.00090). This indicates that the application of the herbicides affects the bacterial population.
Keywords: Herbicides; Microbial Soil population; Soil Toxicity; Paraquat; Glyphosate